Climate change stands as the new challenge for whale watching and North Pacific gray whales (Eschrichtius robustus) in Bahia Magdalena, Mexico, after their recovery from overexploitation - García-Castañeda, Omar; Viloria-Gómora, Lorena; Ávila-Foucat, Véronique Sophie; Vega-Peña, Ernesto Vicente; Pardo, Mario A.; Quintero-Venegas, Gino Jafet; Urbán R., Jorge; Swartz, Steven; Martínez-Meyer, Enrique (Frontiers in Conservation Science, 2024)
Social-ecological systems (SES) recognize the intricate relationship between human activities and the environment and advocate for comprehensive approaches to address complex environmental issues.This study investigates the factors influencing whale watching, particularly the gray whale (Eschrichtius robustus) in northern Mexico, after significant recovery following overexploitation. Despite reaching a peak in 2015, the eastern North Pacific gray whales experienced unusual mortality events (UME), the most recent from 2019 to 2023, leading to a population decline and historically low calf production in 2022. This decline is evident in the reduced presence of whales and calves in winter breeding lagoons. Concurrently, whale watching has become a significant tourist attraction in these areas. Our objective was to develop a mental model of the SES of gray whale watching, integrating ecological and socioeconomic data to identify key variables and interactions that support system resilience. From an ecological perspective, we analyzed the long-term temporal trends of eight years of gray whale counts in the southernmost breeding and nursing lagoons within the Bahía Magdalena-Bahía Almejas Complex, Mexico. Additionally, we have incorporated the current discussion in the literature about the potential impact of global climate change on gray whale populations. In the socioeconomic subsystem, we used participatory methods, including interviews, surveys, and workshops with government officials, tourism operators, and visitors. We added on-site assessments of compliance with welfare regulations to understand tourism dynamics. Our findings identified as main external stressors the changes in ice levels in feeding areas and sea warming in breeding areas, and as internal stressors the compliance with official regulations and the number of vessels observing whales at the same time, while the key socioeconomic factor of the system was tourist satisfaction, influenced by factors such as the quality of the information provided by operators. Ultimately, our mental model provides a framework for further exploration of relevant interactions and trajectories, offering insights for developing effective management strategies.1.